2005
DOI: 10.1103/physrevd.71.125012
|View full text |Cite
|
Sign up to set email alerts
|

Transition in the spectrum of the topological sector ofϕ24theory at strong coupling

Abstract: We investigate the strong coupling region of the topological sector of the two-dimensional φ 4 theory.Using discrete light cone quantization (DLCQ), we extract the masses of the lowest few excitations and observe level crossings. To understand this phenomena, we evaluate the expectation value of the integral of the normal ordered φ 2 operator and we extract the number density of constituents in these states. A coherent state variational calculation confirms that the number density for low-lying states above th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Figure 5 contains two samples of the high-resolution DLCQ results, which show the degeneracy between odd and even states in the infinite-resolution limit. Low-level excitations at strong coupling can be associated with kink-antikink states [60,61,138]. These may indicate formation of a kink condensate driving the transition to symmetry restoration for the negative mass-squared case.…”
Section: φ 4 2 Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 contains two samples of the high-resolution DLCQ results, which show the degeneracy between odd and even states in the infinite-resolution limit. Low-level excitations at strong coupling can be associated with kink-antikink states [60,61,138]. These may indicate formation of a kink condensate driving the transition to symmetry restoration for the negative mass-squared case.…”
Section: φ 4 2 Theorymentioning
confidence: 99%
“…Two-dimensional φ 4 theory has been a focus for nonperturbative light-front methods from almost the beginning [63,64,58,59,60,61,68], at least partly because the theory provides a relatively simple instance of symmetry breaking and the possible importance of zero modes [57,75]. The phase transition has been studied on the light front [58], and there have been various attempts at the calculation of critical couplings and even critical exponents [71].…”
Section: φ 4 2 Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the first work to investigate this subject is Ref. [10] where it is shown that by Fourier transforming the form factors one observes profiles in b ÿ with kinks and antikinks. In addition to the light-front longitudinal structure of DVCS amplitudes in one-loop QED and meson models, we also present the corresponding structure of the LFWFs of the quantum fluctuations of a lepton to order e 2 in QED.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss here selected recent results obtained with these techniques applied to light-front quantized scalar field theory in 1 + 1 dimensions [19][20][21]. For this application, we did not need to invoke the full effective Hamiltonian apparatus since it proved sufficient to work with the bare Hamiltonian for our physics goals.…”
Section: Scalar Field Theory -Spontaneous Symmetry Breakingmentioning
confidence: 99%